Poly(lactic-co-glycolic acid) Nanoparticles Encapsulating the Prenylated Flavonoid, Xanthohumol, Protect Corneal Epithelial Cells from Dry Eye Disease-Associated Oxidative Stress - Anita Kirti Ghosh; Rubina Thapa; Harsh Nilesh Hariani; Michael Volyanyuk; Sean David Ogle; Karoline Anne Orloff; Samatha Ankireddy; Karen Lai; Agnė Žiniauskaitė; Evan Benjamin Stubbs; Giedrius Kalesnykas; Jenni Johanna Hakkarainen; et al. (MDPI AG, 2021)
Oxidative stress is a known contributor to the progression of dry eye disease pathophysiology, and previous studies have shown that antioxidant intervention is a promising therapeutic approach to reduce the disease burden and slow disease progression. In this study, we evaluated the pharmacological efficacy of the naturally occurring prenylated chalconoid, xanthohumol, in preclinical models for dry eye disease. Xanthohumol acts by promoting the transcription of phase II antioxidant enzymes. In this study, xanthohumol prevented tert-butyl hydroperoxide-induced loss of cell viability in human corneal epithelial (HCE-T) cells in a dose-dependent manner and resulted in a significant increase in expression of the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2), the master regulator of phase II endogenous antioxidant enzymes. Xanthohumol-encapsulating poly(lactic-co-glycolic acid) nanoparticles (PLGA NP) were cytoprotective against oxidative stress in vitro, and significantly reduced ocular surface damage and oxidative stress-associated DNA damage in corneal epithelial cells in the mouse desiccating stress/scopolamine model for dry eye disease in vivo. PLGA NP represent a safe and efficacious drug delivery vehicle for hydrophobic small molecules to the ocular surface. Optimization of NP-based antioxidant formulations with the goal to minimize instillation frequency may represent future therapeutic options for dry eye disease and related ocular surface disease.